Gambaran Pemicu Stress Kerja pada Anggota Polisi Satresnarkoba di Polresta Surakarta - Maya Desvira Riandy; Sri Ernawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
There are many stress triggers experienced by police officers. One of them is a form of pressure at work in the form of stress. In simple terms, stress is a form of a person's response, both physically and mentally, to changes in the environment which they feel can disturb them and cause them to be threatened. The aim of this research is to determine the picture of work stress in the Surakarta Police Narcotics Investigation Unit (SatresNarkoba). This type of research is qualitative with in-depth interviews with respondents. In-depth data collection through 7 members of the Surakarta Police Narcotics Investigation Unit (Satres Narkoba). The analysis used is thematic analysis. The results of this research show that there are different work stress factors for each individual or member of the Surakarta Police Narcotics Investigation Unit (SatresNarkoba), including workload and excessive working hours, as well as work pressure. Based on the research results, it can be concluded that each individual has a level of work stress due to different factors.